Resuscitating the Undead Queer in Stephanie Meyer’s Twilight Saga - Jami McFarland (Journal of Popular Romance Studies, 2016)
Broadly, this is an article about queerness and its relationship to Stephanie Meyer’s gothic romance series, Twilight—a narrative about a supposedly odd and out-of-place girl meeting and falling in love with a vampire (or, more appropriately, a rich, white (super)man living with vampirism). In this article, I engage with both common and uncommon representations of queerness. Following an elucidation of the various conceptualizations of the term ‘queer’ to make clear how the term will be deployed throughout the article, I trace a history of queerness within the vampire genre to locate Meyer’s conceptualization of the vampire within this practice. Aligning vampirism with queerness, I explore the often homosocial and homoerotic histories of the vampire figure. Claiming that Meyer’s heteronormative or, perhaps more appropriately, homonormative vampire largely deviates from a tradition of associating the vampire with the Queer (position), I demonstrate how the construction of Edward Cullen still feeds on the popularly imagined construction of queerness. I argue that Meyer’s hetero-romantic Twilight series can be regarded as participating in the century-old tradition of associating the vampire figure with queer identities and ways of being.